Comparison of the changes in adenine nucleotides of rat liver mitochondria induced by tamoxifen and 4-hydroxytamoxifen - Cardoso, Carla M. P. (2003)
The antiestrogen tamoxifen (TAM) inhibits the growth of different estrogen receptor (ER)-negative cells. Recently, multiple effects of TAM on mitochondrial bioenergetic functions have been pointed to explain its ER-independent cell death mechanisms. We have shown that TAM and its major active metabolite 4-hydroxytamoxifen (OHTAM) induce depolarization of the mitochondrial membrane potential ([Delta][Psi]) and uncouple the mitochondrial respiration, depressing the oxidative phosphorylation efficiency. To clarify the biochemical mechanisms underlying the changes in the regulation of ATP synthesis and yield, in this work we evaluated the alterations of mitochondrial adenine nucleotides induced by both drugs and ascertained whether such changes could reflect a specific inhibition of either the adenine nucleotide translocase (ANT) or the phosphate carrier, as well as the activation of ATP hydrolysis due to [Delta][Psi] depolarization. We found that both antiestrogens caused a concentration-dependent decrease in mitochondrial ATP levels. Mitochondrial ADP and AMP were concomitantly increased with a subsequent decrease in the ATP/ADP or ATP/AMP ratios. The total concentration of adenine nucleotides also changed. Additionally, both drugs decreased the ANT content of mitochondria, inhibited the phosphate carrier and induced ATP hydrolysis. However, the effects of TAM were more drastic than those induced by OHTAM. Therefore, the depletion of ATP might result from an activation of ATP catabolism, as well as from a decrease in the mitochondrial content of ANT and partial inhibition of the phosphate carrier. Our data may explain the ER-independent effects and cytotoxicity of both drugs and, in agreement with other previous studies, suggest that OHTAM is much less toxic to mitochondria than TAM.